Eco-Friendly Concrete Innovation in Civil Engineering - Zahra Ghinaya; Alias Masek (ASEAN Journal of Science and Engineering, 2021)
Recently, the weather changes that have occurred are very unconditioned. This feels natural because it has often been felt, even though the heat that occurs is beyond its limit. This is one of the effects of global warming. Concrete is one of the most widely used materials in construction. In fact, cement production is included in the less environmentally friendly category. The purpose of this study is to find out how research on green concrete and whether it has an impact in the world of civil engineering. This research is using a quantitative method. This research describes only a few of the results of trials conducted by several researchers in the world, which prove that there is environmentally friendly concrete that can be applied and some are not. The results of this study showed that most of the innovation of green concrete is not good enough to be applied in the field. This is because in several studies it has been proven that the mixture in the manufacture of green concrete does not qualify as an aggregate material. The conclusion is that there is no innovation in the manufacture of green concrete that has worked so as not to cause damage to the earth. Therefore, other research on green concrete is very necessary to do.